Plant Germplasm and Extreme Conditions of Outer Space - Fateme Mousavi (فصلنامه علوم و فناوری فضایی, 2023)
The extreme temperature fluctuations and the vacuum of the space environment make growing plants in outer space challenging. To simulate the temperature fluctuations and vacuum conditions associated with space environments, dry tomato seeds were placed in a thermal cycle simulator and vacuum simulator chamber of space systems, respectively. A Bradford method was used to determine the total protein content of each group of seeds. Sodium dodecyl-sulfate polyacrylamide gel electrophoresis was used to separate proteins. The seed of the thermal cycle group had the highest protein content (26 to 31 mg/ml), followed by control seeds (8-10 mg/ml) and the vacuum seeds (4-5.6 mg/ml). The molecular weights of the peptides ranged from 8 to 42 kDa. The intensity of the protein bands was significantly different in the thermal cycle group from the other two groups, and vacuum group had the lowest intensity. Water and oil released from seeds in the vacuum environment resulted in a reduction of protein content. In the thermal cycle group, the total protein content and the intensity of the bands were significantly higher than those treated with the control group, which can be attributed to the degradation of storage proteins involved in seed germination in the control group.